PENGAWASAN PELAKSANAAN FUNGSI RUANG TERBUKA HIJAU - Febri Yuliani, Dina Anggraini, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Supervision of the Implementation of Green Open Space Functions. This study aims to determine the supervision of the implementation of the green open space function of the Pekanbaru City government. This study uses a descriptive qualitative approach with primary data obtained from interviews with informants. The research informants were the head of the green open space, employees of the field of work, community and street vendors. The results of this study indicate that the supervision of the implementation of the green open space function of the daughter of Pekanbaru by the government of Pekanbaru City has not achieved the expected results. Where in the implementation there are factors that can influence the supervision. These factors are communication, human resources, and community participation itself which has not been maximally carried out so that the supervision is also not optimal.